2009
DOI: 10.1016/j.canlet.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors and genomic instability

Abstract: Abstract:Histone deacetylase inhibitors (HDACIs) are a promising new class of anticancer drugs.However, their mechanism of action has not been fully elucidated. Most studies have investigated the effect of HDACIs on the regulation of gene transcription. HDAC inhibition also leads to genomic instability by a variety of mechanisms. This phenomenon, which has been largely overlooked, may contribute to the cytotoxic effects of these drugs. Indeed, HDACIs sensitize DNA to exogenous genotoxic damage and induce the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
80
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 106 publications
(80 reference statements)
1
80
0
1
Order By: Relevance
“…Interestingly, in addition to their effects on gene transcription, HDAC inhibitors also induce effects on mitotic fidelity that are highly comparable with those we observe upon inhibition of CtBP expression or targeting of the CtBP chromatinmodifying complex. These effects include activation of the spindle assembly checkpoint, aberrant chromosomal segregation, failure of cytokinesis and reduced association of chromosomal passenger proteins with mitotic chromatin (Stevens et al, 2008;Eot-Houllier et al, 2009). At present, the mechanisms underlying these effects of HDACs are not known, and may be either through regulation of gene transcription or through direct modification of centromeric chromatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in addition to their effects on gene transcription, HDAC inhibitors also induce effects on mitotic fidelity that are highly comparable with those we observe upon inhibition of CtBP expression or targeting of the CtBP chromatinmodifying complex. These effects include activation of the spindle assembly checkpoint, aberrant chromosomal segregation, failure of cytokinesis and reduced association of chromosomal passenger proteins with mitotic chromatin (Stevens et al, 2008;Eot-Houllier et al, 2009). At present, the mechanisms underlying these effects of HDACs are not known, and may be either through regulation of gene transcription or through direct modification of centromeric chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting chromosome segregation during mitosis may be an important mechanism of the anti-cancer activity of HDAC inhibitors (Eot-Houllier et al, 2009). Other strategies to target the spindle assembly checkpoint, such as the use of aurora B inhibitors, are also under investigation as potential therapeutic strategies (Ditchfield et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a rapidly growing number of nonhistone proteins have been found to be targets for HDACs. 13 Over the past few years, more attention has been drawn to HDACs for two main reasons: first, the relationship between HDACs and several diseases, including cancer, has been confirmed; second, many HDIs are used in clinical and preclinical research as anticancer agents and show satisfying effects. 14 In the present study, we show that chronic administration of valproic acid (VPA), a more selective class I HDI when compared with TSA, 15,16 results in a marked decrease in stellate cell activation in vitro and in vivo and significant reduction in septa formation and fibrogenesis in vivo.…”
mentioning
confidence: 99%
“…Oxidative stress and autophagy have been shown to cause cell death in various types of cancers [35][36][37][38]. A previous study demonstrated that the apoptosis of solid tumor and leukemia cells was induced by the generation of ROS following treatment with an HDAC inhibitor [35]. VPA, a well-known HDAC inhibitor, induced ROS generation in several cancer cells, which was attenuated by NAC treatment [36,39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination treatment resulted in an increased ROS generation and autophagy, which were clearly attenuated by ROS and autophagy inhibitors, respectively (Figures 3 and 4). Oxidative stress and autophagy have been shown to cause cell death in various types of cancers [35][36][37][38]. A previous study demonstrated that the apoptosis of solid tumor and leukemia cells was induced by the generation of ROS following treatment with an HDAC inhibitor [35].…”
Section: Discussionmentioning
confidence: 99%